Separation of microcystins by capillary electrochromatography in monolithic columns - Zeisbergerová, Marta; Kost'ál, Vratislav; Srámková, Markéta; Babica, Pavel; Bláha, Ludek; Glatz, Zdenek; Kahle, Vladislav (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2006)
Contribution on microcystin variant analysis by capillary electrochromatography (CEC) with easily affordable spectrophotometric detection is presented. Two types of reversed-phase capillary columns formed by inorganic or organic polymer monoliths were prepared for this purpose. The analyses were performed isocratically by means of tris(hydroxymethyl) aminomethane (TRIS) buffers of mildly alkaline pH containing 30% (v/v) acetonitrile as the mobile phases. The samples were injected electrokinetically and the analyses were done at the same separation field strength of 500 V/cm. Microcystins were detected at 238 nm. Although both column types differ not only in monolith quality (inorganic versus organic) but also in the length of the aliphatic moiety (C8 versus C12) similar results were achieved. The on-column preconcentration as the encouraging prospect of electrochromatographic technique was also tested. Consequently 5% of column volume was injected in contrast with 0.5% at standard injection scheme resulting in the six times enrichment of the low concentrated cyanobacterial extract at the top of the separation column. From these preliminary results can be seen that the CEC method is fully applicable for rapid microcystin screening.
Keywords: polymery; Peptides, Cyclic; mikrocystiny; vysokoúčinná kapalinová chromatografie; chromatografie micelární elektrokinetická kapilární; Cyanobacteria; Molecular Structure; Polymers; molekulární struktura; Reproducibility of Results; reprodukovatelnost výsledků; sinice; Chromatography, High Pressure Liquid; cyklické peptidy; spektrofotometrie ultrafialová; Microcystins; Spectrophotometry, Ultraviolet; Chromatography, Micellar Electrokinetic Capillary